The Lower Proterozoic Marmorilik Formation, East of Mârmorilik, West Greenland. - Garde, Adam A. (Meddelelser om Grønland, 1978)
The Lower Proterozoic Marmorilik Formation, West Greenland, is situated in the Rinkian orogenic complex. East of Marmorilik its predeformation thickness is more than 2 km. A basal 30-60 m thick elastic unit is followed by over 650 m of banded to massive dolomite marble with accessory calcite, quartz, phlogopite, albite, scapolite, pyrite and graphite; near the base of the formation tremolite is common. Dolomitecalcite marble occurs locally in this unit. The massive dolomite is followed by a thin member of impure calcite marble that is succeeded in turn by ea. 300 m of massive dolomite marble. The upper ea. 650 m of carbonate include ea. 350 m of pure calcite marble. The uppermost 200 m known of the formation consist of semipelite, which also forms thin horizons in the marbles. East of Marmorilik the formation is affected by regional metamorphism of greenschist facies grade. The carbonate-silicate parageneses found are isobarically divariant. The estimated temperature and pressure at the peak of metamorphism are up to 500° and 3000 bars. The general structure of the formation east of Marmorilik is that of an open syncline with an E-W-trending horizontal axis. There are several internal, recumbent tight to isoclinal folds accompanied by thrusts; these do not upset the overall stratigraphic sequence. Both left-lateral transcurrent and normal faulting has affected the area. The Marmorilik Formation forms the host rock of the Black Angel Zn-Pb ore deposit, the structural and stratigraphic position of which is discussed. Also small low-grade sulphide mineralisations occur, which consist of sphalerite, galena and pyrite in varying proportions; chalcopyrite, tennantite-tetrahydrite, boulangerite and ullmanite were also found. The mineralisations are stratabound, but some mobilisation has occurred during deformation and metamorphism. Analyses of Zn, Pb, Cu, Ni, Fe, and Mn from ordinary marbles are presented. The origin of the base metals is syn- or epigenetic. Little evidence is left concerning the origin of the marbles; the calcite marbles may well be remnants of a primary calcium carbonate precursor, and the dolomites are believed to have formed by dolomitisation of the refluction type. There is no reason to invoke other processes in the formation of the carbonates than those that are known to have operated during the Phanerozoic.